Post Natal Exercise for maternal health: Attitude & Practice (Journal of Shaheed Suhrawardy Medical College, 2025)
Background: The postpartum exercise changes the quality of life, physical activity, health, functional capacity, and physical fitness of postpartum women. This study is aimed at analyzing the adherence and practice of PNE.Objective: To evaluate the adherence & practice of Post Natal Exercise (PNE). To analyze the effect of postpartum exercise on maternal health.Methods: A hospital based physical interventional study conducted on 44 postnatal women who admitted for delivery. Data was obtained by interviews with patients and from hospital records.Results: A total of 44 postnatal women were enrolled in the study. Regarding the attitude of PNE, 98.2% of the study population felt that it is essential, regular adherence is needed and they will emphasize others. On analysis of practice of PNE 68.18% responded. Among them 47.73% did exercise and 20.45% did not perform. Within the practiced group 70% performed daily and 30% performed occasionally, 93.3% experienced benefits regarding physical activity. Conclusion: Education and motivation are important for practice of PNE.  Also, obstetricians or health workers may influence continuously for adherence & practice.J Shaheed Suhrawardy Med Coll 2023; 15(2): 12-14